New Isotherm for Multilayer Adsorption of Vapours on Non-Porous Adsorbents - S. Sircar (Adsorption Science & Technology)
A new three-parameter isotherm equation to describe multilayer adsorption of vapours on non-porous adsorbants is derived. The model parameters are the monolayer adsorption capacity ( m ) and two temperature dependent constants, C 1 and C ∞ , which describe the adsorbate-surface interactions in, respectively, the first and the subsequent layers. The model can successfully describe the data for multilayer adsorption of ethanol, benzene and cyclohexane on cabosil in the entire relative saturation pressure range of zero to unity.